Konflik Norma Antara Hukum Adat Minangkabau dan Hukum Pertanahan Nasional: Analisis Yuridis Atas Penerbitan dan Balik Nama Sertipikat Hak Milik Yang Bersumber dari Tanah Pusaka Tinggi - Dini Puspita Sari; Yuslim Yuslim; Hengki Andora (Dinasti Research, 2026)
The conflict of norms between the Minangkabau customary law system and national land law as manifested in Civil Decision Number 155/Pdt.G/2023/PN. CEO. The land object of dispute is the high inheritance of the Andah people who have been bound by the pagang gadai relationship since 1945, so customarily it is not free to be transferred. Nonetheless, a series of buying and selling transactions were carried out by individuals who did not have customary capacity, which ultimately resulted in the issuance of Certificates of Ownership and name change to parties outside the race. Using normative legal research methods and case study approaches, this study analyzes three dimensions of the problem: the validity of the transaction of buying and selling high-quality inherited land that has not been certified, the legality of the issuance of ownership certificates over customary land, and the validity of the process of changing the name of the certificate. The analytical framework used includes the theory of accountability, the theory of legal certainty, and the theory of justice. The results of the study show that the three processes contain multiple legal defects, namely violations of customary authorities, the absence of substantive verification by the National Land Agency (BPN), and the transfer of legal burdens between rights holders who are not in equal status. This study recommends the harmonization of the national land registration mechanism with customary law norms through the obligation of substantive customary verification before the issuance of certificates.